It's all in your head : a guide to understanding your brain and boosting your brain power - Barrett, Susan L.; Espeland, Pamela; Urbanovic, Jackie (Minneapolis, MN. : Free Spirit Pub., 1985)
Discusses the physiology and evolution of the brain, definitions and measuring of intelligence, problem solving, and other related topics. Also includes suggestions for further reading and activities for stimulating creative thinking and other intellectual abilities.
Includes index.
Keywords: Brain -- Juvenile literature; Intellect -- Juvenile literature; Brain; Intellect